THE INFORMATION ABOUT GRAPH OF FUNCTION IN THE SUBJECT PHYSICS AND THEIR HIERARCHICAL STRUCTURE - HORVATHOVA, Daniela; ZELENICKY, Lubomir (Trends in education, 2009)
The article deals with the information presented by the graph of function in the subject physics and its hierarchical structure. The results were proved by broad research and defended by competent committees.
Keywords: information; graph of function; hierarchical structure; subject physics.